ECOLOGICAL CONSEQUENCES OF SOIL SALINIZATION - Safarov, Anvar Abdinazarovich (SCIENCE and SOCIETY, 2026)
This article discusses the environmental problems arising from soil salinization. In particular, the impact of salinization on soil composition and physicochemical properties, such as a decrease in soil fertility, negative changes in plant growth and development, as well as a decrease in crop yields, are analyzed. In addition, the impact of salinization on food security and recommendations for eliminating this problem are also described.
Keywords: soil salinization; soil fertility; agricultural crops; productivity; food security